2023
DOI: 10.1088/1674-1056/ac8726
|View full text |Cite
|
Sign up to set email alerts
|

Improving resolution of superlens based on solid immersion mechanism

Abstract: Super-resolution imaging with superlens has been one of the fundamental research topics. Unfortunately, the resolution of superlens is inevitably restrained by material loss. To address the problem, we introduce the solid immersion mechanism into the slab superlens and the cylindrical superlens. The proposed solid immersion slab superlens (SISSL) and the solid immersion cylindrical superlens (SICSL) can improve resolution by converting evanescent wave to propagating wave using high refractive index materials. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…In 1989, Coullet et al introduced the concept of optical vortices in the framework of the Maxwell-Bloch model [3] , and Allen et al first demonstrated OAM in vortex beams with nonparaxial approximation propagating [4] . As our understanding and discussion of optical vortex deepens [5,6] , various applications have also been gradually developed, including but not limited to wave manipulation [7,8] , superresolution imaging [9][10][11] , holography [12,13] , and quantum information processing [14,15] . In particular, tremendous progress has been made in metamaterials and metasurfaces in recent years [16][17][18] , pushing the development of OAM-based applications and devices to new heights, such as OAM efficient generation [19][20][21] , utilizing whisperinggallery modes to achieve theoretical verification of optical OAM [22,23] , OAM multiplexing and demultiplexing [24] , and the spin-to-OAM conversion [25] .…”
Section: Introductionmentioning
confidence: 99%
“…In 1989, Coullet et al introduced the concept of optical vortices in the framework of the Maxwell-Bloch model [3] , and Allen et al first demonstrated OAM in vortex beams with nonparaxial approximation propagating [4] . As our understanding and discussion of optical vortex deepens [5,6] , various applications have also been gradually developed, including but not limited to wave manipulation [7,8] , superresolution imaging [9][10][11] , holography [12,13] , and quantum information processing [14,15] . In particular, tremendous progress has been made in metamaterials and metasurfaces in recent years [16][17][18] , pushing the development of OAM-based applications and devices to new heights, such as OAM efficient generation [19][20][21] , utilizing whisperinggallery modes to achieve theoretical verification of optical OAM [22,23] , OAM multiplexing and demultiplexing [24] , and the spin-to-OAM conversion [25] .…”
Section: Introductionmentioning
confidence: 99%